Depletion of signal recognition particle 72kDa increases radiosensitivity. Issue 6 (3rd June 2017) - Prevo, Remko; Tiwana, Gaganpreet S.; Maughan, Timothy S.; Buffa, Francesca M.; McKenna, W. Gillies; Higgins, Geoff S.
ABSTRACT: The identification of genetic determinants that underpin tumor radioresistance can help the development of targeted radiosensitizers or aid personalization of radiotherapy treatment. Here we identify signal recognition particle 72kDa (SRP72) as a novel gene involved in radioresistance. Knockdown of SRP72 resulted in significant radiosensitization of HeLa (cervical), PSN-1 (pancreatic), and T24 (bladder), BT-549 (breast) and MCF7 (breast) tumor lines as measured by colony formation assays. SRP72 depletion also resulted in the radiosensitization of normal lung fibroblast cell lines (HFL1 and MRC-5), demonstrating that the effect is not restricted to tumor cells. Increased radiosensitivity was not due to impaired DNA damage signaling or repair as assessed by γ-H2AX foci formation. Instead SRP72 depletion was associated with elevated levels of apoptosis after irradiation, as measured by caspase 3/7 activity, PARP-cleavage and Annexin-V staining, and with an induction of the unfolded protein response. Together, our results show that SRP72 is a novel gene involved in radioresistance.